Progress in nuclear astrophysics of east and southeast Asia - Abdul Aziz, Azni; Ahmad, Nor Sofiah; Ahn, S; Aoki, Wako; Bhuyan, Muruthujaya; Chen, Ke-Jung; Guo, Gang; Hahn, K.I; Kajino, Toshitaka; Kassim, Hasan Abu; Kim, D; Kubono, Shigeru; et al. (Springer Nature, 2021)
Nuclear astrophysics is an interdisciplinary research field of nuclear physics and astrophysics, seeking for the answer to a question, how to understand the evolution of the universe with the nuclear processes which we learn. We review the research activities of nuclear astrophysics in east and southeast Asia which includes astronomy, experimental and theoretical nuclear physics, and astrophysics. Several hot topics such as the Li problems, critical nuclear reactions and properties in stars, properties of dense matter, r-process nucleosynthesis, and ν-process nucleosynthesis are chosen and discussed in further details. Some future Asian facilities, together with physics perspectives, are introduced.